Future-Proofing AI Talent in The United States: The Role of Academia in Meeting Industry Demands - Vengathattil, Sunish (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
The rapid growth of technology has created a strong demand for skilled professionals, requiring universities to adapt their programs to meet industry needs. This paper examines the role of higher education, especially in the United States, in preparing students for the future workforce by addressing key challenges such as keeping curricula up to date, securing research funding, and providing hands-on training. To tackle these issues, universities are introducing specialized programs, encouraging interdisciplinary learning, and building stronger partnerships with industries to close the skills gap. Additionally, new educational tools are being used to personalize learning and better equip students for technology-driven careers. This paper emphasizes that continuous innovation in higher education is essential to developing a well-prepared, industry-ready workforce, helping the U.S. maintain its leadership in the global economy.